PERSEPSI BU NYAI TERHADAP KASUS KEKERASAN DALAM RUMAH TANGGA PERSPEKTIF HUKUM ISLAM DAN UNDANG-UNDANG NOMOR 23 TAHUN 2004 - Masulatul Mabruroh (Sekolah Tinggi Agama Islam Miftahul Ulum Lumajang, 2024)
Domestic violence is still a problem in Muslim family law. Some believers allow a husband to beat his wife if he does not want to perform his duties. However, the Law No. 23 of 2004, which regulates the elimination of domestic violence, shows the Indonesian government’s concern for the number of cases of violence in the household. This research uses the type of empirical yuridic research with case qualitative descriptive and legislative approaches. Bu nyai’s perceptions of domestic violence is twofold. First, Bu Nyai considers that the KDRT is a prohibited action, because Islamic law considers it to be a forbidden behavior that is strengthened by the dismissal of the law number 23 of 2004 which clearly and decisively abolished the KDRT. Second, Bu Nyai considers that the KDRT is permitted. In Islamic law, the ability to beat must be with the presence of boundaries and conditions that have been agreed upon by religious scholars because its purpose is to educate.According to the law number 23 of 2004 KDRT is a prohibited act and can essentially be used as a reason to demand divorce.